Fruit and vegetable intake as a moderator of the association between depressive symptoms and cigarette smoking. Issue 4 (1st October 2016) - Haibach, Jeffrey P.; Homish, Gregory G.; Collins, R. Lorraine; Ambrosone, Christine B.; Giovino, Gary A.
ABSTRACT: Background: Studies have consistently reported associations among depression, cigarette smoking, and fruit and vegetable intake (FVI). This study evaluated FVI as a moderator of the association between depressive symptoms and smoking. Methods: The authors analyzed data from the National Longitudinal Survey of Youth 1979: Child and Young Adult. The study sample was adults aged 19–33 years at baseline in the year 2004 from the Young Adult Survey portion. Moderation analyses were performed using the Johnson-Neyman technique to assess whether baseline FVI moderated the association between depressive symptoms and smoking status cross-sectionally and as a predictor of smoking cessation longitudinally at 4-year follow-up. Results: Cross-sectionally, at lower levels of FVI (<4.9 times/day), there was a significant association between smoking and depressive symptoms ( P < .05), but not at higher levels of FVI (≥4.9 times/day; P > .05). Longitudinally, there was an inverse association between depressive symptoms and quitting smoking at FVI <1.2 times/day ( P < .05), but there was not a significant association at FVI ≥1.2 times/day ( P ≥ .05). Conclusions: FVI moderated the association between depressive symptoms and cigarette smoking cross-sectionally and longitudinally. The cross-sectional findings might be partially explained by the longitudinal findings paired with prior research; there might be fewer smokers with high FVI because depressive symptoms are removed as an impediment to cessation. Further experimental research is warranted to test the efficacy of increased FVI as an adjunct to smoking cessation, with a possible mechanism of action being reduced depressive symptoms during quit attempts.